2011
DOI: 10.2319/040710-195.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orthodontic treatment, midline position, buccal corridor and smile arc on smile attractiveness

Abstract: Objective: To assess the scientific evidence of the influence of some variables on smile attractiveness: orthodontic treatment, midline position, axial midline angulation, buccal corridor, and smile arc. Materials and Methods: Literature was searched through PubMed, Web of Science, Embase, and All EBM Reviews. The inclusion criteria consisted of studies written in English; published in the past three decades; concerning the influence of orthodontic treatment, midline position, axial midline angulation, buccal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
2
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 27 publications
9
84
2
16
Order By: Relevance
“…[9][10][11][12][23][24][25][26] However, studies on the buccal corridor with nonmanipulated photographs 13,27 have failed to report a correlation between the buccal corridor and smile attractiveness. Janson 6 recently reviewed previous articles on this matter and concluded that images of actual patients are more acceptable SMILE ATTRACTIONS than digitally altered smiles. Therefore, we utilized nonmanipulated photographs of Japanese orthodontic patients to analyze smiles and found no significant difference between groups A and B for Width-4 (right buccal corridor 7,8,13,16 ), Width-5 (left buccal corridor 7,8,13,16 ), Width-6 (right posterior corridor 13 ), and Width-7 (left posterior corridor 13 ) evaluated by the dental students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][23][24][25][26] However, studies on the buccal corridor with nonmanipulated photographs 13,27 have failed to report a correlation between the buccal corridor and smile attractiveness. Janson 6 recently reviewed previous articles on this matter and concluded that images of actual patients are more acceptable SMILE ATTRACTIONS than digitally altered smiles. Therefore, we utilized nonmanipulated photographs of Japanese orthodontic patients to analyze smiles and found no significant difference between groups A and B for Width-4 (right buccal corridor 7,8,13,16 ), Width-5 (left buccal corridor 7,8,13,16 ), Width-6 (right posterior corridor 13 ), and Width-7 (left posterior corridor 13 ) evaluated by the dental students.…”
Section: Discussionmentioning
confidence: 99%
“…5 Subsequently, an increasing number of studies have focused on the frontal smile. 6 These studies have examined a variety of components of frontal posed smile attractiveness in both vertical and transverse dimensions. However, clinically valuable items for objectively analyzing treatment goals have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang 11 , en el 2010 en su estudio de percepción según el géne-ro y la cara encontró menor tolerancia a las desviaciones en modelos femeninos que en los masculinos, las evaluadoras fueron más tolerantes en desviaciones de modelos masculinos; el presente estudio tuvo uno de los grupos evaluadores conformado por un 80% de mujeres (no relacionadas a la odontología) y el sujeto evaluado fue masculino, y este grupo evaluador de mayoría femenina brindó mayor tolerancia a las desviaciones en el único modelo (masculino). Existen revisiones sistemáticas, de Witt 18 y de Janson 6 , en el 2011, que hallaron que la mayoría de las personas comunes son capaces de detectar desviaciones de 3 mm, pero en cuanto a preferencias eligen las líneas medias coincidentes. Janson 6 en su revisión obtuvo el valor de 2,2 mm de promedio aceptado de desviación de línea media por personas comunes y ortodoncistas; en el presente estudio, las personas no relacionadas a la odontología toleran desviaciones de hasta 3 mm en el lado derecho.…”
Section: En El 2006 Kokichunclassified
“…Existen revisiones sistemáticas, de Witt 18 y de Janson 6 , en el 2011, que hallaron que la mayoría de las personas comunes son capaces de detectar desviaciones de 3 mm, pero en cuanto a preferencias eligen las líneas medias coincidentes. Janson 6 en su revisión obtuvo el valor de 2,2 mm de promedio aceptado de desviación de línea media por personas comunes y ortodoncistas; en el presente estudio, las personas no relacionadas a la odontología toleran desviaciones de hasta 3 mm en el lado derecho.…”
Section: En El 2006 Kokichunclassified
See 1 more Smart Citation